Geography of Taverns of the Lower Wisconsin River Way - Christopherson, Kasey; Berens, Charlie; Hamilton, Martin (My University, 2009)
The Lower Wisconsin River Way is a beautiful and unique area of Wisconsin. Many small communities are located on either side of the Wisconsin River. In and around these communities there are many local establishments which provide a common place for people to gather and enjoy food, beer, and entertainment. The tavern has been a gathering place for people as long as it has been around. In the Lower Wisconsin River Way taverns are places where the local clientele and tourists alike gather to discuss everything from recent sporting events, the year's crops, or most often, the weather. We came to the understanding that people go to taverns to get away from the outside world to a place where they can relax enjoy a cocktail, a meal, or the company of others. Every unique tavern can be a reflection of the people it attracts and the community it resides in. We believe that you cannot tell a book by its cover, but after our observations we believe you can tell quite a bit about a town by its tavern or taverns. Communities throughout the Lower Wisconsin River Way harbor a strong sense of heritage that's reflected in the drinking and dining culture. Whether it's a small town like Blue River that caters almost exclusively to the local crowd, or a large community like Prairie Du Chien with many taverns, an idea of heritage, and a sense of community resonates in the town's taverns. The differences in the communities are reflected in the taverns who adorn these towns.
Chart included.
Keywords: Lower Wisconsin Riverway; Taverns